Few-layered titanium trisulfide (TiS3) field-effect transistors. Issue 29 (1st July 2015) - Lipatov, Alexey; Wilson, Peter M.; Shekhirev, Mikhail; Teeter, Jacob D.; Netusil, Ross; Sinitskii, Alexander
Abstract : Titanium trisulfide (TiS3 ) whiskers can be mechanically exfoliated and used for fabrication of field-effect transistors, which upon coating with Al2 O3 exhibit mobilities up to 43 cm 2 V −1 s −1 and ON/OFF ratios up to 7000. Abstract : Titanium trisulfide (TiS3 ) is a promising layered semiconductor material. Several-mm-long TiS3 whiskers can be conveniently grown by the direct reaction of titanium and sulfur. In this study, we exfoliated these whiskers using the adhesive tape approach and fabricated few-layered TiS3 field-effect transistors (FETs). The TiS3 FETs showed an n-type electronic transport with room-temperature field-effect mobilities of 18–24 cm 2 V −1 s −1 and ON/OFF ratios up to 300. We demonstrate that TiS3 is compatible with the conventional atomic layer deposition (ALD) procedure for Al2 O3 . ALD of alumina on TiS3 FETs resulted in mobility increase up to 43 cm 2 V −1 s −1, ON/OFF ratios up to 7000, and much improved subthreshold swing characteristics. This study shows that TiS3 is a competitive electronic material in the family of two-dimensional (2D) transition metal chalcogenides and can be considered for emerging device applications.